The evolving relationship between mathematics and cryptology, 1951–1952: SCAG and the beginnings of SCAMP and NSASAB. Issue 4 (4th July 2017) - Christensen, Chris
ABSTRACT: World War II proved the value of using mathematicians as codebreakers. Both the Army's Signal Intelligence Service (SIS) and the Navy's OP-20-G recruited mathematicians. When the war ended and demobilization occurred, some of these mathematicians accepted academic positions or positions in industry, but some continued to serve as codebreakers. In the early 1950s, the Armed Forces Security Agency (AFSA) struggled with Soviet ciphers and with the United States' communications intelligence (COMINT) needs for the Korean War. In 1951, in the face of a seemingly intractable problem with a Soviet cipher machine called Albatross, AFSA established a group of consultants, the Special Cryptologic Advisory Group (SCAG), which consisted of academic and industrial mathematicians and engineers. The year-long experience with SCAG led, in 1952, to AFSA's establishment of a summer program, Special Committee Advising on Mathematical Problems (SCAMP), which enlisted academic mathematicians to work on Agency problems, and it also led to the establishment of the NSA Scientific Advisory Board (NSASAB). This article explores the immediate post-World War II evolution of the relationship between academic mathematicians and the NSA that is reflected in SCAG and in the beginnings of SCAMP and NSASAB.